Effects of Tax Revenue and Capital Expenditure on Economic Growth : A Case Study of the Union Territory of Puducherry, India - Basumatary, Joel (Arthshastra Indian Journal of Economics & Research, 2022)
The growth effects of the government’s own tax revenue and capital expenditure were estimated for the Union Territory of Puducherry using the ordinary least squares multivariate regression model for 2005–2018. The results suggested that both government’s own tax revenue and capital expenditure had significant positive effects on the economic growth of the Union Territory. For example, one unit increase in capital expenditure could boost economic growth (NSDP) by 13%. Similarly, one unit change in the government’s own tax revenue collection could potentially change the NSDP of the Union Territory by 30%. Therefore, the Puducherry government can focus on increasing its capital expenditure to enhance its economic growth. Similarly, it can increase its own tax revenue (the taxes under its jurisdiction) by broadening its tax base. These may help the government boost its growth and thus correct its internal fiscal imbalance.